Development of the Family-Based Care Model for Stroke Survivors to Promote Healthy Family Dynamics: Participatory Action Research - Piyarat Chaknum; Teeranut Harnirattisai; Chomchuen Somprasert; Li-Chi Chiang (Pacific Rim International Journal of Nursing Research, 2023)
In many cultures around the world, including those in Thailand, family caregivers have different views on caring for stroke survivors. These views affect the caring process, which tends to be a heavy burden for caregivers. This study used participatory action research to develop the Family-Based Care Model for Stroke Survivors to Promote Healthy Family Dynamics. Stroke survivors and their family caregivers were recruited via purposive sampling from two primary care units in Nonthaburi, Thailand. Fourteen caregivers participated in four cycles of activities for 16 weeks and they were divided into two groups of seven. Data were collected using family group discussions, observations, home visits, telephone, LINE application, and field notes, as well as a family demographic questionnaire. Participants in each group created caregiving strategies to balance family life tailored for stroke survivors’ families. Individual and collective self-reflective cycles were used as a method that contained four steps: planning, acting, observing, and reflecting. Qualitative data were analyzed using the ATLAS.ti 8.0 program to develop data categorization and themes. The four major themes emerged and described the participatory process in caring stroke survivors: 1) Assessing problems and developing strategies; 2) Making collaboration for changing strategies; 3) Balancing the body and mind to empower themselves; and 4) Healthy family dynamics. This study demonstrated that there were five main phenomena affecting care: caregiver characteristics, family functions and relationships, assistant support, community resources, and community nurses. The model developed in this study can help direct nurses to promote healthy family dynamics in Thai stroke survivors, however, it is necessary to be further tested through research before being applied in practice.